Comparison of pregnancy outcome between immigrant women in couples with same ethnicity to mixed ethnicity couples. (1st November 2020) - Avraham, Sarit; Zakar, Liat; Maslovitz, Sharon; Zoabi, Jenna; Lavie, Anat; Yogev, Yariv; Many, Ariel
Abstract: Aim: To compare the pregnancy outcome of immigrant women who became pregnant to the same ethnicity partner versus a partner from a different ethnicity. Methods: A retrospective cohort study on all singleton pregnancies of immigrant women who delivered between the years 2011–2015 in a single tertiary University Affiliated Hospital. Demographic and obstetrical data were collected. Same ethnicity couples and mixed couples were compared using the Pearson chi-square test for dichotomous variables, and Student's T -test for normally distributed continuous variables. Results: Overall, 443 immigrant women delivered during the study period, of them, 294 (66.37%) had the same ethnicity spouse and 149 (33.63%) were part of a mixed couple. Women of same ethnicity couples were significantly younger (32.7 versus 35.05 years, p  < .0001) and more likely to be nulliparous (48 versus 32%, p  = .001), compared to women of mixed couples. The rate of episiotomy was significantly higher among women with the same ethnicity spouse in comparison to women of mixed couples (37.22 versus 23.85%, p  = .01). There was no significant difference in all other obstetrical or perinatal outcomes tested. Conclusions: Maternal component is the main factor for perinatal outcomes among immigrant mothers.